Intermediate Structures in Fission and Consequences on Average Partial Cross Sections - Bouland Olivier H. (EPJ Web of Conferences, 2013)
This paper is willing to illustrate and quantify the impact of a double fission barrier in terms of average fission cross section and in particular, to status on both the additional class-II width correction factor and the degree of freedom of the overall double fission barrier which is a key parameter in the calculation of the standard Wn,f factor of Hauser-Feshbach theory.